2008
DOI: 10.3357/asem.2126.2008
|View full text |Cite
|
Sign up to set email alerts
|

Decompression Illness Reported in a Survey of 429 Recreational Divers

Abstract: In our study population, the lifetime incidence of DCI was increased in divers with less diving experience. If further studies confirm this finding, diving federations should be encouraged to intensify their efforts of educating divers and should limit diving time and depth in inexperienced divers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…16 In addition, the previous experience of divers has been related to the risk for DCI. 17 Moreover, air travel after diving courses increases the risk for development of DCI, probably due to the high-pressure alterations. 18…”
Section: Decompression Sicknessmentioning
confidence: 99%
“…16 In addition, the previous experience of divers has been related to the risk for DCI. 17 Moreover, air travel after diving courses increases the risk for development of DCI, probably due to the high-pressure alterations. 18…”
Section: Decompression Sicknessmentioning
confidence: 99%
“…Nevertheless, our results are consistent with previous studies that have reported lower intravascular bubbles counts in females and a higher incidence of DCS in male divers. 9,14,28 DATA SPECIFIC TO FEMALES…”
Section: Decompression Sicknessmentioning
confidence: 99%
“…8 Research suggests that only about 10% of divers experience some form of DCS in their lifetime. 9,10 However, for divers with a PFO the overall risk of DCI doubles, for neurological DCS it increases fourfold, and for divers with a large PFO, it increases six-fold. 11,12 In order for DCS associated with PFO to occur, at least three conditions need to be met: • Post-dive venous gas emboli must be present.…”
Section: Introductionmentioning
confidence: 99%